METHODOLOGY FOR TEACHING STUDENTS TO MAKE A HUMAN HEAD PATTERN IN A SCULPTURAL LESSON - Allaberganov Ollabergan Davlatyorovich (Web of Journals Publishing, 2023)
In this article, the process of teaching students of pedagogical higher education institutions to work a human head sample in sculptural lesson Sessions is shown in methodological consistency.
Keywords: sculpture, Sinch, proportion, clay, carcass, bench, board.